Incidence of Canine Digestive System Tumours in Baghdad Province - Alabbody, Huda Hameed Kadhim; Lafta, Inam Jasim (The Iraqi Journal of Veterinary Medicine, 2019)
Tumours in pets occur naturally are as common in dogs as they are in humans. Tumours of the alimentary system have been reported in animals, although less frequently. Food patterns and specific diet components could have a big role in such tumour occurrence. Therefore, the aim of this study was to investigate the clinical signs and inspect the neoplasm lesions of the gastrointestinal (GI) tract grossly and histopathologically in dogs in Baghdad, Iraq, and to see whether pet diets had any tumourigenic effect. Throughout two years sixteen dogswere referred to Teaching Animal Hospital and private clinics at Baghdad city had masses in (GI) tract. Males and the large sizes breeds were more likely to be affected with GI tumours. Half of the cases aged 5-10 years and belonged to German Shepherd, while the other half involved the other breeds (i.e. Belgian Malinois, Labrador, Pointer GSP and Terrier) equally. Biopsies were taken from the tumour tissues for histological examination. Clinically, the animals presented general signs of digestive system abnormalities like difficulty defecating, bloody stool, lethargy and weight loss. Grossly, the tumours varied in their sizes from <3 cm to >5 cm in diameter, and the most frequent site of occurrence (10 out of 16 cases) was in the large intestine. Histologically, the most tumours reported were malignant, and included adenocarcinomas (6/16) followed by leiomyosarcoma (4/16), and 2/16 belonged to carcinoid tumour. However, lipoma and viral papilloma (4/16) were also registered as the benign tumours. Inconclusion,tumours of canine digestive system do exist but rare. The healthy nutrition of dog may be prevent this type of tumour when dog consume enough amount of raw meat, little of artificial food like kibble with small of some vegetables and fruits. Additionally, the information gained from dogs could be used to suspect and test the effect on humans as they have strong pathophysiology similarities